Health care system of the Republic of Serbia in the period 2004-2012 - Gajić-Stevanović Milena; Aleksić Jovana; Stojanović Neda; Živković Slavoljub (Serbian Medical Society - Dental Section, Belgrade, 2014)
Introduction. The backbone of Serbian health system forms the public healthcare provider network with 355 institutions and around 112,000 employees, owned and controlled by the Ministry of Health and financed mainly by the Republican Health Insurance Fund. The law recognizes private practice that was not included, till recently, in the public funding scheme. New Health Insurance Law (2005) decreased the number of entitlements in the basic health service package. It abolished the right to dental health care for adults (exceptions are: children, older than 65, pregnant women and emergency cases) as well as the right to compensate travel expenses. The aim of this study was to evaluate the effects of health care system of the Republic of Serbia and indicate parameters that determine the state of health of the population, on the ground of data obtained by the Institute of Public Health of Serbia. Results. In the period 2004-2012, cardiovascular diseases represented the main cause of illness in Serbia (50%). In 2012 digestive system diseases were on the second place. Neoplasm and nervous system diseases were on the third place. From 2007 to 2012 there was slight decline in the birth rate and number of deaths, but the death rate increased from 13.9 to 14.2. Health care system in Serbia is funded through the combination of public finances and private contributions. Primary care is provided in 158 health care centres and health care stations, secondary and tertiary care services are offered in general hospitals, specialized hospitals, clinics, clinico-hospital centers and clinical centres. Conclusion. A significant but not satisfactory progress has been achieved in the field of health status indicators as the most important outcome of the final performance of the health system. The transition of public health care system in Serbia since the communist period to present and slow integration with European Union is unfinished process.